Gadoxetic acid-enhanced MRI combined with T1 mapping and clinical factors to predict Ki-67 expression of hepatocellular carcinoma - Qiu, Ganbin; Chen, Jincan; Liao, Weixiong; Liu, Yonghui; Wen, Zhongyan; Zhao, Yue (Frontiers in Oncology, 2023)
Objectives: To explore the value of gadoxetic acid-enhanced magnetic resonance imaging (MRI) combined with T1 mapping and clinical factors in preoperative predicting Ki-67 expression for hepatocellular carcinoma (HCC). Methods: This retrospective study included 185 patients from two institutions with surgically resected single HCC who underwent preoperative T1 mapping on gadoxetic acid-enhanced MRI. Patients from institution Ⅰ (n = 124) and institution Ⅱ (n = 61) were assigned to training and validation sets, respectively. univariable and multivariable analysis were performed to investigate the association of clinic-radiological variables with Ki-67 labeling index (LI). Then, a prediction nomogram was developed and validated for Ki-67 LI. The performance of the nomogram was evaluated by its calibration, discrimination, and clinical utility. Results: Multivariable analysis showed that alpha-fetoprotein levels > 20ng/ml, neutrophils to lymphocyte ratio > 2.25, non-smooth margin, tumor-to-liver signal intensity ratio in the hepatobiliary phase ≤ 0.6, postcontrast T1 relaxation time > 705 msec were significant independent predictors of Ki-67 LI. The combined model constructed based on these significant variables had the best predictive performance with an area under the receiver operator characteristic curve of 0.899, an area under the precision-recall curve of 0.946 and an F1 score of 0.912, and reached 0.823, 0.879, 0.857 in the validation set. Conclusions: Gadoxetic acid-enhanced MRI combined with T1 mapping and clinical factors has good predictive efficacy for preoperative prediction of Ki-67 LI, which can promote the individualized risk stratification and further treatment decision of HCC patients.